The future without a past : the humanities in a technological society - Russo, John Paul (University of Missouri Press, 2005)
"Argues that technological imperatives like rationalization, universalism, monism, and autonomy have transformed the humanities and altered the relation between humans and nature. Examines technology and its impact on education, historical memory, and technological and literary values in criticism and theory, concluding with an analysis of the fiction of Don DeLillo"--Provided by publisher